Rethinking technodiversity - Yuk Hui (The UNESCO Courier, 2023)
In 1914 during the outbreak of the First World War, the French philosopher Henri Bergson gave an inaugural speech titled “Meaning of the War” as the newly elected president of the Académie des Sciences Morales et Politiques. Bergson, who later became the president of the International Committee on Intellectual Cooperation (the ancestor of UNESCO), accused Germany of “machinism” and “mechanism” – these terms appear many times in his short speech. It was machinism and mechanism which led Germany from being a country of music, poetry and metaphysics, to a “scientific barbary” and “systematic barbary”.